2008
DOI: 10.1017/s1074070800023774
|View full text |Cite
|
Sign up to set email alerts
|

Farm-Level Risk Management Using Irrigation and Weather Derivatives

Abstract: An agronomic crop growth model-the Decision Support System for Agro-Technology Transfer-and a constant relative risk aversion utility function are used to examine corn irrigation strategies in Mitchell County, Georgia. Precipitation contracts are designed to help farmers manage risk. Three conclusions originate from the findings. First, the optimal irrigation strategy can greatly increase producers' certainty-equivalent revenue. Second, changes in water pricing policy would have a limited impact on the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…Irrigation strategies are commonly viewed as yield enhancing, but they are also mitigating the risk of lower yield outcomes (Lin, Mullen, and Hoogenboom, 2008;Senft, 1992). Timing of irrigation applications and the amount of water administered have been two common research topics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation strategies are commonly viewed as yield enhancing, but they are also mitigating the risk of lower yield outcomes (Lin, Mullen, and Hoogenboom, 2008;Senft, 1992). Timing of irrigation applications and the amount of water administered have been two common research topics.…”
mentioning
confidence: 99%
“…Dalton concluded that irrigation strategies provide risk management benefits as risk aversion increases, and federal crop insurance programs were inefficient in reducing exposure to production risk from variable rainfall. The more recent paper by Lin, Mullen, and Hoogenboom (2008) used biophysical simulation to evaluate both risk efficient irrigation levels and the effectiveness of weather derivatives as a risk mitigation tool.…”
mentioning
confidence: 99%
“…Agricultural producers have several methods available to them for hedging their weather-related risks, including insurance and weather derivatives (Turvey, 2001;Schintkey et al, 2003;Lin et al, 2008). Our H1 concerns grain producers' use of hedging instruments, which could include insurance and/or weather derivatives, to mitigate weather risk.…”
Section: Weather Risk Managementmentioning
confidence: 99%
“…This loss distribution is distinct from the empirical distribution used in as it only uses a subset of observations. Consequently following Lin et al (2008), g ( x ) is estimated using a nonparametric kernel density estimator. The payout rates are 70%, 80%, and 60% for tiers 2, 3, and 4 (Figure 1), 85%, 70%, and 0% are the cut offs for tiers 2, 3, and 4, respectively, while μ is the probability that a producer's PM is less than the RM.…”
Section: The Modelmentioning
confidence: 99%